Economic impact of crop management on performance of hybrid and inbred varieties of rice (Oryza sativa) in India: Evidences from farm level study - JANAIAH, A (The Indian Journal of Agricultural Sciences, 2013)
Input output data on-farm trials on hybrid rice (1993-95) collected in Andhra Pradesh, Karnataka, Tamil Nadu, Haryana and punjab and also from farmers who have grown hybrid rice voluntarily 1995 in Andhra Pradesh, was analysed to examine the economic impact of crop management on productivity and profitability of hybrid and inbrea varieties of rice for this purpose, crop management index (MANID) was contructed using non imput and time bound farm operations. Results indicate that hybrid rice outyielded inbred rice by 31.5%(1.8 tonnes/ha) with more adaptability under highly intensive management conditions. Yield gain was only 12% (0.7 tonne/ha) under average management cpmdotopms. The yield MANID relationship indicates nearly 30% higher responsiveness of MANID on hybrid rice yield as compared to that of inred.Yield loss due to poor crop management was 34.5% for hybrids while it was 4% for inbred rice. Hybrid rice ws economically profitable on more intensively managed locations. Futher,yield response functions indicate that marginal efficiency of key inputs like organic manure, fertilizer, plant protection, labour, etc was higher for hybrids than for inbred. This study suggests to focus research on the development of an integrated crop and resource mangement strategy and management insensitive hybrids for relisation of yield potential of currently available gybrid rice technology.